The Role of Motivation, Self-Efficacy, and Peer Support in Driving Student Engagement: Bridging Theory and Practice - Ramlan Mustapha; Shahlan Surat; Azam Syukur Rahmatullah (CV Najmi Edu Creative, 2025)
This study explores the role of motivation, self-efficacy, and peer support in influencing student engagement in higher education, aiming to connect theoretical perspectives with practical applications. A quantitative correlational research design was utilized, involving 223 university students from various faculties. Participants completed validated questionnaires measuring intrinsic and extrinsic motivation, academic self-efficacy, perceived peer support, and student engagement's behavioral, emotional, and cognitive dimensions. Data were analyzed using multiple regression techniques to determine the predictive strength of each variable. Results revealed that motivation and self-efficacy were significant predictors of student engagement, explaining a substantial portion of the variance. Peer support also demonstrated a comparatively more minor positive effect on engagement. These findings highlight the importance of internal psychological and external social influences in enhancing student engagement. The study supports integrating motivation theory and social learning principles into educational practice. Practical implications suggest that educators should foster supportive peer environments while promoting student motivation and confidence to improve learning outcomes. This research contributes to the growing body of literature emphasizing the multifaceted nature of student engagement and offers a foundation for future intervention-based studies in diverse educational settings.